Turkey and the chances of membership in the European Union and the future of the relationship 1950-2015 - Tabtab, Mohammad Mahmoud; Saleh, Wesal Abdullah Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aims to examine the problem of Turkey’s accession to the European Union, as it is one of the most important contemporary issues that raise great controversy inside and outside the European Union. Especially after the entry of European countries, and the opening of negotiations for Turkey to join the European Union in October 2005. Turkey carried out several internal reforms, such as political, economic, and social, and then shed light on the development of the relationship between Turkey and the European Union, and studied the various obstacles and challenges, which Turkey, in its attempts to join it, faced Turkey’s ability to overcome these obstacles by implementing various reforms. To achieve the goal, the researcher followed the historical method, by analyzing the observed European Union data on Turkey, and analyzing the content of many texts and opinions that serve the goal of the study. Therefore, the researcher recommended that Turkey continue its attempts to embarrass the European Union in front of the world in its attempts to join the European Union.